Who's the bigot? learning from conflicts over marriage and civil rights law - McClain, Linda C. (Oxford University Press, 2020)
Charges, denials, and countercharges of bigotry are increasingly frequent in the U.S. Bigotry is a fraught and contested term, evident from the rejoinder that calling out bigotry is political correctness. That is so even though renouncing- and denouncing-bigotry seems to be a shared political value with a long history. Identifying, responding to, and preventing bigotry have engaged the efforts of many people. People disagree, however, over who is a bigot and what makes a belief, attitude, or action bigoted. This book argues that bigotry has both a backward- and forward-looking dimension. We learn bigotry's meaning by looking to the past, but bigotry also has an important forward-looking dimension. Past examples of bigotry on which there is consensus become the basis for prospective judgments about analogous forms of bigotry. The rhetoric of bigotry-how people use such words as "bigot," "bigoted," and "bigotry"-poses puzzles that urgently demand attention. Those include whether bigotry concerns the motivation for or the content of a belief or action; whether reasonableness is a defense to charges of bigotry; whether the bigot is a distinct type, or whether we are all a bit bigoted; and whether "bigotry" is the term society gives to beliefs that now are beyond the pale. This book addresses those puzzles by examining prior controversies over interfaith and interracial marriage and the recent controversy over same-sex marriage, as well as controversies over landmark civil rights law and more recent conflicts between religious liberty and state antidiscrimination laws protecting LGBTQ persons"--